Derechos del paciente y su relación con la atención de enfermería en el Área de Cirugía del Hospital Isidro Ayora - Gómez Salgado, Diana Margarita (2015)
The patient’s rights constitute a fundamental part in health care and the nursing staff is considered as an essential element to defend it and guarantee their practice. The present investigation determined the fulfillment of patient’s rights regarding nursing care in the surgical area of the “Isidro Ayora” General Hospital, identifying at the same time the patient knowledge of such rights and the generated satisfaction during their hospitalization. The study corresponded to an investigation of a descriptive type whose sample was formed by 171 patients hospitalized in the service. The investigation shows that regarding the six rights established in the Protection of the Patient Law the rights practiced more frequently are: the right to dignified care, the right not to be discriminated, the right to confidentiality and the right to emergency attention; however, there are shortcomings in the fulfillment of the right to information and the right to decide, mostly at the moment to request the patient the consent to practice simple and complex procedures. The majority of patients do not know which are their rights as users of the service, and only a few of them has received information about them by the nursing staff, as a result almost half of patients is partially satisfied with the attention regarding the fulfillment of their rights. KEY WORDS: Patient’s rights, dignified attention, satisfaction.